Optimizing the internal control at BASNAZ to Mitigate Fraud Risks with COSO Cube Model (Study Case of Bandar Lampung’s BAZNAS) - Putri, Cyntika Desmita Sabilla; Sulhani, Sulhani (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the effectiveness of the internal control system of Sharia accounting at the National Zakat Agency (BAZNAS) of Lampung City in order to increase public trust. Given the important role of public trust in the continuity of BAZNAS operations, the problem of corruption is a major concern. The corruption case involving the BAZNAS treasurer in Bengkulu in 2022 and in East Tanjung Jabung, Jambi in 2023 is the background of this study. Using a qualitative descriptive analysis method, data was collected through literature studies and semi-structured interviews with two sources: Head of the Secretariat Mr. Doni Peryanto and the Finance and Reporting Division Mrs. Nurma Yulia. Interviews were conducted using the COSO model to ensure clear boundaries and data validity. The results of the study indicate that the control environment, control activities, risk determination, and information and communication at BAZNAS Lampung City have been running effectively but still need improvement. Recommendations for improvement include the implementation of an oath for all employees, stricter employee selection, stricter expenditure authorization procedures, and the provision of financial reports on the website and employee assessments based on key performance indicators. This study provides insight into internal control optimization steps to improve transparency and accountability of BAZNAS Lampung City.